Inhibition of Corrosion of Carbon Steel in Well Water by DL-Phenylalanine-Zn2+ System - A. Sahaya Raja; S. Rajendran; P. Satyabama (Journal of Chemistry)
The environmental friendly inhibitor system DL-phenylalanine-Zn2+ has been investigated by weight loss method. A synergistic effect exists between DL-phenylalanine and Zn2+ system. The formulation consisting of 150 ppm of DL-phenylalanine and 5 ppm of Zn2+ offers good inhibition efficiency of 90%. Polarization study reveals that this formulation functions as a anodic inhibitor. AC impedance spectra reveal that a protective film is formed on the metal surface. The surface morphology has been analysed by SEM and EDAX. A suitable mechanism of corrosion inhibition is proposed based on the results obtained from weight loss study and electrochemical studies.